DETERMINANT FACTORS TOWARDS THE COMPETITIVENESS OF PINEAPPLE AGROINDUSTRY IN PANGKALPINANG - Miranty Dhea Putri (Socio-Economics/Agribusiness Department, 2017)
This study aimed to analyze the determinant competitiveness factors of agro-industry Pineapple in Pangkalpinang and to analyze the relationship between components in these factors in favor of agro-industry cluster growth pineapple. This study was conducted in September 2016 up to March 2017 in Pangkalpinang. The data are obtained from a survey. The sample size used in this study are 47 respondents. The analytical method used is descriptive analysis, Delphi techniques, and the porter's diamond model analysis. The results of this study found that the determinant factors in the competitiveness of pineapple agro-industry in Pangkalpinang Municipality are the role of government factor and the opportunity factor. While the factors that have average influence are strategy, structure and competition factor, demand factors, and factors related and supported industries. The relationship among the factors is clear that labor and raw material are closely related to internal strength and the major components for growing the pineapple agroindustry cluster are demand factor, strategy, structure in the industry and the rivalry.